getOA 1.2 - A Semantic Search Tool for Learning Objects in Repositories with Portuguese Language Support - Silva, Josivan Pereira da; Silveira, Ismar Frango (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Search strategies for Learning Objects (LOs) in repositories, by using purely syntactic structures, can make that task of searching and retrieval become time-consuming and unproductive, and consequently can decrease the possibilities for reuse of these resources. The present work has as its main goal to use generic-purpose thesauri of the Portuguese language to establish semantic structures in the search for LOs. For this purpose, an architecture proposal is presented, as well as the development of a semantic search tool based on thesauri and federated search at three distinct repositories with Portuguese language support. The results show improvements in the search and the increase of the quantities of the recovered LOs. The semantic search tool is available for download under GNU 3 license.